Standard Bearers: Material Culture and Middle-Class Communities at the Turn of the Twentieth Century - Moskowitz, Marina (Enterprise & Society, 2000)
A generation of historians, working at the intersection of business history and cultural history, has examined the consumer culture that flourished in the United States in the nineteenth and twentieth centuries. In studies of advertising, marketing, department stores, credit systems, and other aspects of selling and buying, these scholars have shown that American businesses not only produced consumer goods but also created consumer desire.
Keywords: Business History and gender